Literature Review Efektifitas Terapi Garam Terhadap Pengobatan Granuloma Umbilikalis - Fitriya, Wahida; Fitriani, Aice Bela; Diba, Farah; Rohmini, Samsi; Helma; Ida Sofiyanti (Universitas Ngudi Waluyo, 2023)
Umbilical granuloma (UG) is a major problem in neonates and young babies. This usually occurs in mothers due to continuous leakage of secretions in the umbilicus area after separation. Delayed treatment of granulomas continues to flow and causes persistent irritation over a long period of time, up to weeks. Several management modalities for umbilical granuloma include; using cooking salt, granuloma ligation, uterization and surgical excision. Umbilical granuloma is granular tissue that grows prominently in the center of the navel after the baby's umbilical cord falls off. Umbilical granuloma is reported to occur in 1 in 500 newborns. A literature study was conducted to determine the effectiveness of salt therapy in treating umbilical granulomas. The criteria for the articles reviewed were articles within the year 2020-2023 and used the Google Scholar database. The keywords used are